Self Medication Drugs During The Covid-19 Pandemic At Pharmacy - Aryani, Fina; Amalia, Annisa Yuri; Djohari, Meiriza; Humairah, Anugrah (Poltekkes Kemenkes Riau, 2024)
Corona Virus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-Cov2) with a high mortality rate. Self-medication is the behavior of taking self-medication based on a diagnosis of the symptoms of illness that occurs. This study aims to determine the profile of the use of self-medication drugs that are often used to treat symptoms similar to COVID-19 during the COVID-19 pandemic at the Pekanbaru City Pharmacy, Riau Province in the period of July 2021. The type of research is observational with a descriptive design and concurrent data collection. The population is the respondent who self-medicates in a pharmacy in Pekanbaru. The sample is 100 respondents who have met the inclusion criteria with a purposive sampling technique. The results showed that the most used drugs were for fever symptoms (27.8%), the most pharmacological class of drugs purchased by patients were antipyretics-analgesics (32.5%), the most used dosage forms were tablets (58, 7%). During the self-medication process, patients most often received information from health workers (35.4%). Based on gender, the most patients who self-medicated were women (56%), the age of the most patients was around 17-25 years (46%), while from the last education level the most patients were high school/equivalent (44%) with the type of work as private employees (48%). Drugs that are often purchased during the Covid-19 pandemic are analgesics-antipyretic.